2018
DOI: 10.1021/acs.jpcc.8b07348
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Elementary Steps of Transport of Xylene Mixtures in ZSM-5 Zeolites

Abstract: The transport of p-xylene in purely siliceous MFI was investigated in the presence of coadsorbed m-xylene by combining fast time-resolved IR spectroscopy and frequency response methods. p-Xylene transport rates are dominated by diffusion in the straight channels of MFI, which is 8 times faster than transport in the sinusoidal channels. m-Xylene adsorbed on the outer surface lowers the sorption rate of p-xylene significantly by blocking pore entrances, whereas m-xylene adsorbed in the MFI pores hardly influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…From perspective of a reduced ethanol partial pressure by increasing nitrogen flow, there is a reduced probability to adsorption / re‐adsorption and therefore a reduction of the average reaction chain length from ethanol to the major product fraction. Consequently, for both considerations, ethanol partial pressure and contact time, coke precursors and aromatics should be reduced. From the perspective of different power laws of interconverting chemical reactions, there is a strong tendency to effective power 1 for small aromatics because of diffusion limitations [22] . A change in nitrogen flow should not affect the flow regimes too much, but the contact time. Discussion for speed‐up of power 2 molecular reactions as discussed for bimolecular hydride transfer and cyclization and observed maxima in coke and aromatics formation is complementary to the discussion of the reaction chain length.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From perspective of a reduced ethanol partial pressure by increasing nitrogen flow, there is a reduced probability to adsorption / re‐adsorption and therefore a reduction of the average reaction chain length from ethanol to the major product fraction. Consequently, for both considerations, ethanol partial pressure and contact time, coke precursors and aromatics should be reduced. From the perspective of different power laws of interconverting chemical reactions, there is a strong tendency to effective power 1 for small aromatics because of diffusion limitations [22] . A change in nitrogen flow should not affect the flow regimes too much, but the contact time. Discussion for speed‐up of power 2 molecular reactions as discussed for bimolecular hydride transfer and cyclization and observed maxima in coke and aromatics formation is complementary to the discussion of the reaction chain length.…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of different power laws of interconverting chemical reactions, there is a strong tendency to effective power 1 for small aromatics because of diffusion limitations [22] . A change in nitrogen flow should not affect the flow regimes too much, but the contact time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Miniaturization of ZSM-5 crystals down to nanometer scale and generation of hierarchically porous structure have been found to be effective to enhance the transport property,a cid site accessibility and catalytic performances. [4] Especially,a s molecules diffuse more rapidly along the straight channels than within the sinusoidal channels, [5] fort he large pore dimension and low tortuosity,decrease of zeolitic domain size preferentially along b-axis is more influential to boost transport and catalytic properties.F or instances,s ignificant enhancement of catalyst lifetime and selectivity in methanol-togasoline (MTG) [6] and methanol-to-olefin (MTO) [7] conversions have been demonstrated when b-axis was reduced to asingle unit cell thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, diffusion is directly proportional to the concentration of pore openings at the external surface and the p -xylene surface concentration. We have shown that the co-adsorption of m -xylene on the external surface reduces the overall p -xylene transport rate on MFI at 373 K by reducing the concentration of pore openings available for the p -xylene transport . However, it remains unclear, by what mechanism m -xylene blocks sorption sites as adsorption of m- and p- xylene is equilibrated.…”
Section: Introductionmentioning
confidence: 95%